And then there were none: what a UCU archive tells us about employee relations in marketising universities. Issue 12 (1st December 2020) - Kuznetsova, Olga; Kuznetsov, Andrei
ABSTRACT: Our study engages evidence from a University and College Union branch archive to explore developments in employee relations (ER) that reflect the organisational effects of marketisation of UK universities. The evidence exposes points of strain in ER at a level of professional divide between managers and academics, and helps to understand their roots in the context of universities as organisational hybrids. Our investigation reveals the failure of ER to adapt to increasingly conflict-ridden working environments and encourages a different, sustainability-centred, approach to constructing ER in universities in an attempt to coordinate more effectively the clashing institutional logics.